Criminal Organizations and Hybrid Governance in South America: The COVID-19 scenario - Ferreira, Marcos Alan (2022)
This essay discusses how criminal organizations in South America have reconfigured themselves in the face of the pandemic scenario experienced since late 2019. In particular, it examines how the practices and actions carried out by these associations were carried forward in the pandemic, maintaining or even giving force the influence of crime on the life of South American society. It is argued that in order to understand criminal governance, it is essential to consider the discussion of how the territories in which these organizations operate are not in conflict with the state, but rather there is a hybrid governance in which criminal organizations and the state coexist as two sources of legitimacy. and authority. There is a complementarity of actions, in which criminal organizations were seen during the pandemic occupying state functions in the adoption of protective measures, and provision of assistance, but always with a clear objective of maintaining the status quo of their illicit activities. In the end, it is clear that criminal organizations have consolidated themselves as a governance space recognized as legitimate during the pandemic, complementing and, perhaps even, eclipsing the role of state bureaucracy in the face of the seriousness of the health emergency experienced, especially in the cases of Brazil and Colombia.